Correlation Between Personal Hygiene of Handlers With The Presence of Escherichia Coli In Meatball at Palangka Raya University - Martani, Natalia Sri; Jabal, Arif Rahman; Turnip, Oktaviani Naulita; Teresa, Astrid; Silalahi, Angelina Brigitta Darawulan (Barigas: Jurnal Riset Mahasiswa, 2025)
Food handlers have the opportunity to transmit disease. Meatballs are one of the most popular foods, however if the sanitary hygiene facilities of the place, the hygiene of meatball processing, and the personal hygiene of the handler are poor, it is vulnerable to bacterial contamination, one of which is Escherichia coli. This study aims to determine the relationship between personal hygiene of the handler with the presence of Escherichia coli in meatballs at Palangka Raya University. This study used a correlation study design with a cross-sectional approach and the sampling technique was carried out with a total sampling technique involving 14 meatball sellers as research samples. The instruments used in this study were observation sheets and laboratory tests. Data analysis used chi-square test. The results showed that 12 respondents did not fulfill Kepmenkes RI No.492/MENKES/SK/VII/2003 and based on laboratory tests, 4 meatball samples were positive for Escherichia coli bacteria. Based on the results of statistical tests, the results of this study prove that there is no relationship between personal hygiene of the handler with the presence of Escherichia coli bacteria in meatballs